2020
DOI: 10.3390/f11121247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Modification on the Nano-Mechanical Properties of the Wood Cell Wall and Waterborne Polyacrylic Coating

Abstract: Masson pine (Pinus massoniana Lamb.) samples were heat-treated at different treatment temperatures (150, 170, and 190 °C), and the nano-mechanical properties of the wood cell wall, which was coated with a waterborne polyacrylic (WPA) lacquer product, were compared. The elastic modulus (Er) and hardness (H) of wood cell wall and the coating were measured and characterized by nanoindentation, and the influencing factors of mechanical properties during thermal modification were investigated by chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…For instance, the following results are reported: H NI = 0.35–0.42 GPa for Pinus massoniana Lamb. In [ 107 ], H NI = 0.41–0.53 GPa for Masson pine , coinciding within the measurement accuracy for EW and LW in [ 108 ] and H NI = 0.34–0.54 GPa for Pinus taeda , not discerning EW and LW, in [ 109 ]. Similar results are reported for H NI in cell walls junction through the middle lamella for Norway spruce .…”
Section: Cells and Cell Wallssupporting
confidence: 63%
“…For instance, the following results are reported: H NI = 0.35–0.42 GPa for Pinus massoniana Lamb. In [ 107 ], H NI = 0.41–0.53 GPa for Masson pine , coinciding within the measurement accuracy for EW and LW in [ 108 ] and H NI = 0.34–0.54 GPa for Pinus taeda , not discerning EW and LW, in [ 109 ]. Similar results are reported for H NI in cell walls junction through the middle lamella for Norway spruce .…”
Section: Cells and Cell Wallssupporting
confidence: 63%
“…Besides, due to the similarity of cell walls' microstructure, nanohardness H n variations within the same sample and even between different wood species are not large. For instance, the measurements of H n in various pine species give the following values: 440-490 MPa for Pinus sylvestris L. [37], 350-420 MPa for Pinus massoniana Lamb., as reported in [38], and 410-530 MPa [39] and 340-540 MPa for Pinus taeda [40].…”
Section: Methodsmentioning
confidence: 63%
“…The study of the effective distribution of Young's modulus and microhardness based upon indentations with size corresponding to that of several cells revealed that the mechanical properties differences between early and late wood annual ring layers (Figures 6-8) were several times larger than those measured in cell walls at the nanoscale, which are usually around 10-20% [37][38][39]. Besides, the former technique require much less surface preparation and does not require a precise indentation targeting cell walls whose width is in the order of several micrometers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, в [40] в клеточных стенках сосны обыкновенной (Pinus sylvestris L.) H c в молодой древесине (7-е годовое кольцо) составляла в EW 439 МРа, а в LW -466 МРа; в зрелой древесине (74-е годовое кольцо) в EW -469 МРа, а в LW -489 МРа. В [61] в сосне (Pinus massoniana Lamb.) твердость клеточной стенки варьировалась в интервале 0.35−0.42 GPa независимо от того, была ли ее внутренняя полость заполнена пластиком при ламинировании или нет.…”
Section: материалы и методыunclassified